(3GdefJNH aj GdSjGSI hGdCOHs - (3CHh ehSi GdGjfYjs ((3Ydi Hf CMeO GdTGhi GdcThWi s)
(3ChdgG (B:s
(3hHYO aEf CHhGH gPG GdcJGH GdefJNH ai GdSjGSg hGdCOH NeSI hCQHYhf HGHkG s
(3BNQgG (B:s
(3jG CMeb Gh cCfc CYde ef GdWHjH, aVMc GdWHjH hGfUQa s
(3HBNQgG Jedc SfI (B1100 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B105 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B(91 (3b(B) s
Keywords: (3GdCOHs